Entry in the presence of dueling options - Folta, Timothy B.; O'Brien, Jonathan P. (Strategic Management Journal, 2004)
Abstract This paper investigates the influence of industry uncertainty on the decision by established firms to enter a new industry. Specifically, we examine the tension between the option to defer , which discourages entry in the presence of uncertainty, and the option to grow , which may encourage entry in the presence of uncertainty when there are early mover advantages. Empirical analysis on data from a broad array of industries revealed that the effect of uncertainty on entry is not monotonic. Our findings are the first to find support for the nonmonotonic effect of uncertainty that has only recently emerged in theoretical treatments of real options theory, and amplify the importance of considering both the option to defer and the option to grow when contemplating entry. Furthermore, we found evidence that the relationship between uncertainty and entry is moderated by: (a) irreversibility, which influences the value of the option to defer; (b) the total value of growth opportunities; and (c) early mover advantages, which magnify the value of growth options. Copyright © 2003 John Wiley & Sons, Ltd.